2014
DOI: 10.1039/c4cp00593g
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle neutron scattering study of micropore collapse in amorphous solid water

Abstract: Vapor-deposited amorphous solid water (ASW) is the most abundant solid molecular material in space, where it plays a direct role in both the formation of more complex chemical species and the aggregation of icy materials in the earliest stages of planet formation. Nevertheless, some of its low temperature physics such as the collapse of the micropore network upon heating are still far from being understood. Here we characterize the nature of the micropores and their collapse using neutron scattering of gram-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 73 publications
(95 reference statements)
6
49
2
Order By: Relevance
“…While the relative volume of the pores does not change drastically during the warm-up of the ices, the total surface decreases by a factor 3.5 between 10 and 120 K, influencing the increase in average pore size. This is consistent with a recent study from Mitterdorfer et al (2014) who show, by using small angle neutron scattering of ASW ice deposited at 77 K, that the specific surface area decreases from 90 to 100 K. The pores present in our simulations reach these Fig. 3.…”
Section: Pore Volume and Surface Areasupporting
confidence: 82%
“…While the relative volume of the pores does not change drastically during the warm-up of the ices, the total surface decreases by a factor 3.5 between 10 and 120 K, influencing the increase in average pore size. This is consistent with a recent study from Mitterdorfer et al (2014) who show, by using small angle neutron scattering of ASW ice deposited at 77 K, that the specific surface area decreases from 90 to 100 K. The pores present in our simulations reach these Fig. 3.…”
Section: Pore Volume and Surface Areasupporting
confidence: 82%
“…It is well known that ASW might be deposited in a porous form, which depends on deposition angle, rate and temperature (Dohnalek et al, 2003;Hill et al, 2016;Kimmel et al, 2001a, b;Kouchi et al, 1994;Mayer and Pletzer, 1986;Mitterdorfer et al, 2014;Raut et al, 2007;Stevenson et al, 1999). Deposition of ASW at temperatures between 90 and 110 K revealed either small degrees of porosity (Brown et al, 1996;Chonde et al, 2006) or were nonporous (Kimmel et al, 2001b;Stevenson et al, 1999).…”
Section: The Effect Of Nano-crystalline Ice On the Vapor Pressurementioning
confidence: 99%
“…Furthermore, it has been shown that faster deposition enhances the porosity and leads to a slower sintering process [15], which raises the question whether the pores in our sample could remain intact even when annealing to temperatures where significant sample desorption already takes place?…”
Section: Resultsmentioning
confidence: 99%
“…One obvious candidate for such defects in ASW are molecules in the vicinity of pores. ASW can be a highly porous solid, with a pore size distribution which strongly depends on the deposition conditions [15,16]. Pores in ASW are characterized by dangling OH bonds of molecules located close to the pores, hence, the different slow relaxation rates or the appearance of a fast relaxing component (or both phenomena) seen in figure 2, could perhaps be related to a high density of pores when growing at 52K, which reduces for higher growth temperatures of ASW and disappears when growing well above the crystallization temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation